In the meanders of memory. Tensions and contentions of play - Rizolli, Marcos (Revista ARA, 2022)
The memory of childhood, almost always, claims light, naive and uncommitted memories. In the scenario we are, the adult mind – almost elderly – was challenged by the boy's voice to perform a memorial tour, in an invitation to review the layers of my time. So, with my art, drawings were produced in graphite and sepia on paper (with subsequent digital treatment) to produce a diegetic imagery. As maybe Warburg would like, I created a small atlas of playing to, in some way, answer what Didi-Huberman would have asked: what are emotions?